Seismic Demands in Column Base Connections of Steel Moment Frames. Issue 3 (August 2018) - Torres-Rodas, Pablo; Zareian, Farzin; Kanvinde, Amit
Methods for the seismic design of base connections in steel moment frames are well-developed and routinely utilized by practicing engineers. However, design loads for these connections are not verified by rigorous analysis. This knowledge gap is addressed through nonlinear time history simulations using design-level seismic excitation that interrogate demands in column base connections in 2-, 4-, 8-, and 12-story steel moment frames, featuring base connections that reflect current U.S. practice. The results indicate that: (1) for exposed base plate connections, lower bound (rather than peak) estimates of axial compression are suitable for design because higher axial forces increase connection strength by delaying base plate uplift; (2) even when designed as pinned (as in low-rise frames), base connections carry significant moment, which can be estimated only through accurate representation of base flexibility; and (3) the failure of embedded base connections is controlled by moment, which may be estimated either through overstrength or capacity-based calculations.